2016
DOI: 10.1016/j.amsu.2015.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Are we following an algorithm for managing chronic anal fissure? A completed audit cycle

Abstract: BackgroundAnal fissure is one of the commonest proctological diseases with considerable national variation in sequential treatment. We aimed to audit our compliance of chronic anal fissure (CAF) management with national guidance provided by the Association of Coloproctology of Great Britain and Ireland (ACPGBI).MethodsWe retrospectively audited patients presenting to outpatient clinics with CAF over a 6-month period. Using electronic patient records, notes and clinic letters, we compared their management with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Farkas et al . conducted an audit using the Association of Coloproctology of Great Britain and Ireland (ACPGBI) position statement as the standard and reported that 43.9% adhered to guidelines. Further, they demonstrated that compliance with the ACPGBI treatment algorithm was significantly correlated with success without surgery compared to using non‐compliant methods (83.3% vs 26.1%, Fisher's exact test, P = 0.00004).…”
Section: Discussionmentioning
confidence: 99%
“…Farkas et al . conducted an audit using the Association of Coloproctology of Great Britain and Ireland (ACPGBI) position statement as the standard and reported that 43.9% adhered to guidelines. Further, they demonstrated that compliance with the ACPGBI treatment algorithm was significantly correlated with success without surgery compared to using non‐compliant methods (83.3% vs 26.1%, Fisher's exact test, P = 0.00004).…”
Section: Discussionmentioning
confidence: 99%
“…According to British Coloproctology Protocol, if the medication therapy does not heal the wound after 6-8 weeks, botulinum injection is recommended. 11 If the wound does not heal after 2-3 months from injection, then lateral internal sphincterotomy will be performed for patient. These steps may take about 8-9 months.…”
Section: Discussionmentioning
confidence: 99%
“…An anal fissure is a longitudinal, oval, ulcer-like tear in the anal canal that can extend from the dentate line to the anal verge [59][60][61][62][63]. In almost 90% of cases, the anal fissures are observed in the posterior midline and cause pain during defecation and/or bleeding due to hypertonia of the internal anal sphincter, which results in ischemia.…”
Section: Anal Fissurementioning
confidence: 99%
“…Topical or oral calcium channel blockers can be used as an alternative of topical nitrates. These are considered as first-line treatments for chronic anal fissures [59][60][61][62].…”
Section: Anal Fissurementioning
confidence: 99%